Enhancing Vocabulary Acquisition in EFL Students through Captioned Audiovisual Debate Sessions - Gaetan Olivier; Nunung Suryati; Sari Karmina (Universitas Tidar, 2025)
Teaching and learning the English vocabulary pose considerable challenges for both EFL instructors and learners. However, vocabulary is a crucial component that must be mastered in the process of language acquisition. Thus, this study aims to investigate the substantial effect of captioned audiovisual debates in English on vocabulary acquisition among EFL learners. In this study, the researchers employed a quantitative method, specifically a one-group pretest-posttest research design, along with five perception-based questionnaires. The study was conducted at the English Department of Universitas Negeri Malang, East Java, with 39 undergraduate students in semesters 3 and 5 as the subjects of the study. The findings revealed that captioned audiovisual debate session material has a significant positive effect on the vocabulary acquisition of learners of English as a foreign language in the Universitas Negeri Malang, Indonesia. The t-test results indicate a remarkable difference in students' vocabulary knowledge performance between the pretest and posttest, in terms of both receptive and productive vocabulary skills, after watching the captioned debate video session. Meanwhile, the value of the t-test for receptive vocabulary knowledge was -5.082, and for productive vocabulary was -8.620, which was less than the alpha value of 0.05, presenting significance. It can be concluded that using captioned audiovisual debate can potentially enhance the vocabulary knowledge of EFL students.